2019
DOI: 10.1007/s12088-019-00835-9
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus sabdariffa Extract Inhibits Adhesion, Biofilm Initiation and Formation in Candida albicans

Abstract: Microbial biofilms act as reservoirs for pathogenic sessile microbes which reside inside the three dimensional matrix of the biofilm, and are thus protected against anti-microbial drugs. Most of the anti-microbial drugs fail to completely abolish the biofilm associated infections. In the present study, we provide evidence of Hibiscus sabdariffa (Hs) extract having possible anti-microbial activity, with emphasis on Candida albicans biofilm. The Hs extract was shown to be effective against C. albicans pre-formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A couple of studies have previously reported the antimicrobial potential of H.s. [ 31 , 32 ]. Baena-Santillán et al [ 31 ] have recently determined and compared the antimicrobial effect of H.s.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of studies have previously reported the antimicrobial potential of H.s. [ 31 , 32 ]. Baena-Santillán et al [ 31 ] have recently determined and compared the antimicrobial effect of H.s.…”
Section: Resultsmentioning
confidence: 99%
“…The H.s. extract was also able to inhibit the adhesion, biofilm initiation, and formation of the yeast Candida albicans [ 32 ]. We have previously demonstrated the effect of a plant extract against the Gram-positive strains Staphylococcus aureus and Listeria monocytogenes [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many essential oils and extracts from plants have also been found to inhibit adhesion of C. albicans, but their active compound is generally unknown, as they are composed of complex, unidentified mixtures of both polar and nonpolar natural compounds [105][106][107][108][109].…”
Section: Carbohydrate Derivativesmentioning
confidence: 99%
“…After four h incubation, 66.32% of hyphal form was seen in the control group, while 3.96%, 2.11% and 1.65% of hyphae were formed in the presence of CFL, FAL and FAB, respectively [ 140 ]. As reported by Dwivedi et al [ 141 ], the Hibiscus sabdariffa L. (Malvaceae) flower DMSO extract inhibited the yeast-to-hypha transition with hyphae showing morphological changes, and also adherence of C. albicans cells (80% at 6.25 mg/mL). It also inhibited biofilm formation as well as disrupted the pre-formed C. albicans biofilm by 50% when tested at 3.12 mg/mL.…”
Section: Reported Antibiofilm Activities Of Eos Propolis and Extracts From Plants Algae And Cyanobacteriamentioning
confidence: 61%